Potentials of Internet of Things for effective public relations activities: Are professionals ready? - Lanre Amodu; Oladokun Omojola; Nelson Okorie; Babatunde Adeyeye; Evaristus Adesina (Cogent Business & Management, 2019)
The research explored public relations professionals' views on the potentials of adoption of the Internet of Things (IoT) for their functions. High level of competitiveness in business engendered by globalization and technological advancement has made relationship-building sacrosanct to business survival. The advent of Internet-based communication has increased the sophistication of the target audience of public relations, which requires a matching upgrade of the technological versatility of practitioners. Decisions on customer satisfaction are increasingly based on data and the best sources of data are the customers themselves. Consequently, the IoT offers an unprecedented avenue for data gathering through the 'assistance' of customers themselves. This study, therefore, adopted an online survey to evaluate the views of 100 public relations professionals on their need for IoT, and a t-test was used to analyse the data. The findings revealed that independent public relations firms or agencies were more likely to adopt IoT for their activities than in-house departments. It was recommended that public relations professionals should explore actively the benefits of IoT for advanced operations.
Keywords: 650; Communication; Internet of Things; Internet Relations of Things; public relations; smart-PR